TINJAUAN HUKUM TERHADAP PERCERAIAN KARENA MURTAD MENURUT HUKUM POSITIF - Bhudiman, Budy; Ratnawaty, Latifah (YUSTISI, 2021)
In the Compilation of Islamic Law, Article 75, one of the verses states that the decision to annul a marriage is not retroactive to a marriage that is canceled because one of the husband or wife is an apostate. Children born from such marriages and third parties as long as they obtain their rights in good faith, before the decision to annul the marriage is legally binding. If Muslims act as apostates or change religions, there will be changes and consequences in terms of muamalah, namely three, namely in the marriage relationship, inheritance rights, and guardianship rights. Law Number 1 of 1974 concerning Marriage is a legal unification in conducting marriage to the resolution of various problems that arise in marriage, must refer to Law Number 1 of 1974 concerning Marriage and Law Number 9 of 1975 concerning the Implementation of Law Number 1 of 1974 concerning Marriage. By Article 39 paragraph 2 of Law Number 1 of 1974 concerning Marriage in conjunction with Article 19 of Law Number 9 of 1975, it does not regulate any reasons for divorce due to apostasy but in the Islamic Law Compilation, the reasons for divorce due to apostasy are regulated in Article 116 letter h. AbstrakDi dalam Kompilasi Hukum Islam Pasal 75 salah satu ayatnya menyatakan bahwa keputusan pembatalan perkawinan tidak berlaku surut terhadap: perkawinan yang batal karena salah satu suami atau istri murtad. Anak-anak yang dilahirkan dari perkawinan tersebut dan pihak ketiga sepanjang mereka memperoleh hak-hak dengan ber'itikad baik, sebelum keputusan pembatalan perkawinan berkekuatan hukum yang tetap. Jika orang Islam bertindak murtad atau berpindah agama maka terdapatlah perubahan-perubahan dan akibat dalam segi muamalah yaitu ada tiga yaitu dalam hubungan perkawinan, hak waris dan hak kewalian. Undang-Undang Nomor 1 Tahun 1974 tentang Perkawinan merupakan unifikasi hukum dalam menyelenggarakan perkawinan sampai dengan penyelesaian berbagai permasalahan yang timbul didalam perkawinan, harus merujuk pada Undang-Undang Nomor 1 Tahun 1974 tentang Perkawinan dan Undang-Undang Nomor 9 Tahun 1975 tentang Pelaksanaan Undang -Undang Nomor 1 Tahun 1974 tentang Perkawinan. Sesuai dengan Pasal 39 ayat 2 Undang-Undang Nomor 1 Tahun 1974 tentang Perkawinan juncto Pasal 19 Undang-Undang Nomor 9 Tahun 1975, tidak mengatur adanya alasan perceraian karena murtad namun didalam Kompilasi Hukum Islam alasan perceraian karena murtad diatur didalam Pasal 116 huruf h.